Inhibition test of moringa seeds extract against the growth of Staphylococcus aureus - Ali Yusran; Utari Ayu Wardana (Makassar Dental Journal PDGI Makassar, 2020)
Background: One of natural materials used to prevent oral cavity infections caused by bacteria is Moringa plant extracts. The ingredients contained in Moringa plants are phenolic, alkaloid, tannin, and pterygospermin is thought to be able to inhibit bac-terial growth. Staphylococcus aureus has been known for a long time as a pathogen in the medical field but only a few studies were carried out in the oral cavity. Objective: To determine the inhibition test of Moringa oleifera L extract towards the growth of S.aureus bacteria. Method: The S.aureus culture was inserting on the surface of the nutrient so that it had solidified in a petri dish. Moringa seed extract was diluted in concentrations of 5%, 10%, 20%, and 40%. Paper disks are placed on agar me-dia contained populations of S.aureus bacteria, and after 24 hours the inhibition zone were measured. Results: The average diameter of inhibition zone at concentrations of 5%; 10%; 20%; 40% are 6.7 mm, 7.21 mm, 7.23 mm, 7.6 mm consecutively. Conclusion: A concentration of 5% Moringa oleifera L extract can inhibit the growth of S.aureus bacteria.